2018
DOI: 10.1016/j.envexpbot.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of terpene synthase gene expression in Eucalyptus globulus leaves upon ozone and wounding stresses: relationships with stomatal ozone uptake and emission responses

Abstract: Ozone and wounding are key abiotic factors but, their interactive effects on temporal changes in terpene synthase gene expression and emission responses are poorly understood. Here, we applied combined acute ozone and wounding stresses to the constitutive isoprenoid-emitter Eucalyptus globulus and studied how isoprene, 1,8-cineole, and isoledene synthase genes were regulated, and how the gene expression was associated with temporal changes in photosynthetic characteristics, product emission rates, and stomatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Furthermore, with atmospheric CO 2 and temperatures increasing at unprecedented rates, it is important to investigate how different climatic factors will influence FPC concentrations, and the impact this may have on ecological and commercial systems. Previous studies have shown that environmental stresses related to climate change—such as elevated atmospheric CO 2 and ozone—can increase specialized metabolite concentration in Eucalyptus (Gleadow et al, 1998; Kanagendran et al, 2018). Our improved method to detect and quantify FPCs will allow future studies to investigate how those compounds respond to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with atmospheric CO 2 and temperatures increasing at unprecedented rates, it is important to investigate how different climatic factors will influence FPC concentrations, and the impact this may have on ecological and commercial systems. Previous studies have shown that environmental stresses related to climate change—such as elevated atmospheric CO 2 and ozone—can increase specialized metabolite concentration in Eucalyptus (Gleadow et al, 1998; Kanagendran et al, 2018). Our improved method to detect and quantify FPCs will allow future studies to investigate how those compounds respond to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Volatile organic compounds can vary drastically depending on several other factors [59]. Among these, abiotic and biotic stresses have affected the emission rate of the hydrophilic oxygenated monoterpene 1,8-cineole in Eucalyptus globulus Labill., through the regulation of terpene synthase and stomatal conductance [60]. The emission rates of the same compound were found to be also lightand temperature-dependent in Pinus sylvestris L. [61], Hesperis matronalis L. [62] and Pinus pinea L.…”
Section: Influence Of Cultivation Substrate On Vocsmentioning
confidence: 89%
“…In parallel and without any further stress event, a slower response builds up within 5-15 h which needs ∼1-2 days to fade out. However, the pattern has not been observed in all investigations which might partly be related to methods that are too coarse to detect such fast responses (Behnke et al, 2009;Pazouki et al, 2016;Acton et al, 2018;Kanagendran et al, 2018a). In these cases, normally only the second peak is described in the publication.…”
Section: Model Development and Parameterizationmentioning
confidence: 98%